Natural Tourism Potential for Sport Tourism Activities in the Bengkayang Regency Area - Syahadatina; Zusyah Porja Daryanto; Nevi Hardika (UNIB Press, 2023)
This study aims to develop an effective game-based volleyball learning model at Sungai Kakap 21 state elementary school. The research method used is development research. The stages of the research include needs analysis, and designing learning models, Bengkayang Regency has quite interesting natural tourism potential to carry out sport tourism activities. Here are some natural attractions in Bengkayang Regency which can become sport tourism destinations: 1. Lake Sentarum is the largest lake in West Kalimantan and is one of the most popular natural attractions in Bengkayang Regency. This lake presents beautiful scenery and offers various sports tourism activities such as fishing, water cycling, and traveling by boat. 2. Bathing Waterfalls: There are several waterfalls in Bengkayang Regency that can become sport tourism destinations, such as the Bathing Waterfalls located in Jawak Village, Siding District. In this place, tourists can do rafting and trekking activities. 3. Gunung Palung Protected Forest is an ideal place for hiking and trekking activities. Here, tourists can enjoy beautiful natural scenery and see various types of flora and fauna that live in the forest. 4. Tanjung Netherlandsng Beach is a beach located in Lubuk Landai Village, Sejuang District. Here, tourists can do surfing and snorkeling activities. Those are some of the natural tourism potentials in Bengkayang Regency which can become sport tourism destinations. In addition, Bengkayang Regency also has unique culture and traditions, such as Dayak dances and various festivals which can be a special attraction for tourists who are looking for a different cultural experience.